PUBLIC TRUST (TRUST IN SERVICE) TERHADAP E-GOVERNMENT PENGAWASAN INSPEKTORAT PADA PENGGUNAAN DANA DESA DI KABUPATEN BUTON TENGAH - La Ance Paulus; Rulinawaty; Adrian Tawai (Halu Oleo University, 2025)
This study examines trust in service towards e-government in the Inspectorate’s oversight of village fund utilisation in Buton Tengah Regency. The implementation of e-government aims to enhance transparency and accountability in financial governance. However, its effectiveness depends on the level of public trust in the system. Using a qualitative case study approach, this research analyses community and village officials' perceptions of the Inspectorate’s supervision through the Siswaskeudes application. The findings indicate that transparency, accessibility, and responsiveness play crucial roles in building public trust. Survey results show that the majority of respondents have a high level of trust in the system, particularly in its responsiveness (49.59% very trusting, 50.41% trusting), transparency (49.59% very trusting, 49.59% trusting), efficiency (58.54% very trusting, 41.46% trusting), and simplicity (39.84% very trusting, 58.54% trusting). However, challenges remain, including limited technological infrastructure, varying levels of digital literacy, and concerns regarding the Inspectorate’s independence. The study highlights that improving e-government services, addressing technical limitations, and increasing public participation in monitoring processes are essential for strengthening public trust. These findings provide valuable insights for policymakers to enhance digital-based oversight mechanisms and ensure more transparent and accountable village fund management.